PENINGKATAN KETERAMPILAN KEWARGANEGARAAN (CIVIC SKILLS) MELALUI PENERAPAN STRATEGI PEMBELAJARAN BERBASIS MASALAH - Mukhamad Murdiono (Jurnal Penelitian Ilmu Pendidikan, 2010)
This research aims to increase the active participation of students in the learning process and civic skills who owned the students through the application of problem-based learning strategies. Civic skills is an essential component to have the student as the embodiment of good citizens. This research is a proactive classroom action research by Schmuck (1997). These research subjects are students and the Department of Preschool and Primary Education, Faculty of Education, State University of Yogyakarta who take courses in basic concepts of Civic Education. Data collected through observation, interviews, and documentation and analyzed by reflecting the observations during the implementation of the action. Data validity checking technique used is the technique of triangulation. The results of this study indicate that the application of problem-based learning strategies in the learning of citizenship can enhance the active participation of students in the learning process. Increasing the active participation of students in the learning process makes the process of teaching and learning can take place effectively. In addition, through this method can improve the civic skills of students that possess. It can be seen from the increasing ability to perform analysis of problems that have been identified by each group. Keywords: Civic Skills, Problem-Based Learning